Integrated learning and health: A call for increasing coordination efforts. Issue 2 (2nd April 2016) - Chafouleas, Sandra M.; Polifroni, E. Carol
Abstract : This commentary reinforces a call to recognize the need for substantive collaboration, communication, and cooperation across education and health sectors. Themes throughout the body of articles contained in the special issue are discussed as strengthening knowledge about the benefits to integration of education and health domains in prevention and intervention. A brief review of coordinated school health efforts in the United States is provided, with discussion related to increasing the roles of student services personnel in leading coordination. Finally, recommendations are made to move the conclusions provided in the issue around the what for potential foci of prevention and intervention to greater focus on the how in integration and sustained implementation in diverse contexts and across broad systems.